Nix Plays a Neuroprotective Role in Early Brain Injury After Experimental Subarachnoid Hemorrhage in Rats - Zhang, Juyi; Yuan, Guiqiang; Liang, Tianyu; Pan, Pengjie; Li, Xiang; Li, Haiying; Shen, Haitao; Wang, Zhong; Chen, Gang (Frontiers in Neuroscience, 2020)
Nix is located in the outer membrane of mitochondria, mediates mitochondrial fission and implicated in many neurological diseases. However, the association between Nix and subarachnoid hemorrhage (SAH) has not previously been reported. Therefore, the present study was designed to evaluate the expression of Nix and its role in early brain injury (EBI) after SAH. Adult male Sprague-Dawley (SD) rats were randomly assigned to various time points for investigation after SAH. A rat model of SAH was induced by injecting 0.3 ml of autologous non-heparinized arterial blood into the prechiasmatic cistern. The expression of Nix was investigated by Western blot and immunohistochemistry. Next, Nix-specific overexpression plasmids and small interfering RNAs (siRNAs) were separately administered. Western blot, neurological scoring, Morris water maze, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining and fluoro-jade B (FJB) staining were performed to evaluate the role of Nix in EBI following SAH. We found that Nix was expressed in neurons and its expression level in the SAH groups was higher than that in the Sham group, which peaked at 24 h after SAH. Overexpression of Nix following SAH significantly decreased the expression of translocase of outer mitochondrial membrane 20 (TOMM20, a marker of mitochondria), ameliorated neurological/cognitive deficits induced by SAH, and reduced the total number of apoptotic/neurodegenerative cells, whereas siRNA knockdown of Nix yielded opposite effects. Taken together, our findings demonstrated that the expression of Nix is increased in neurons after experimental SAH in rats, and may play a neuroprotective role in EBI following SAH.